THE NOVEL INVALIDNI SOUROZENCI (DISABLED SIBLINGS) AS A GUIDE TO THE SEMIOSPHERE OF THE UNDERGROUND - Hosek, Adam (Bohemica Olomucensia, 2021)
The article explores the role of the novel Invalidni sourozenci by Egon Bondy in the semiotic space of the Czech underground during its formative period in the mid 1970s. It is viewed through Jurij Lotman's comparison between semiosphere and a museum exhibition.
Keywords: Underground; Egon Bondy; Invalidni sourozenci; semiosphere; cultural semiotics